Hukum Menikahkan Anak Perempuan Luar Nikah oleh Ayah Biologisnya Menurut Imam Syafi’i dan Imam Hanafi - Ihsan Siregar; Muhammad Amar Adly (JURNAL ILMIAH RESEARCH STUDENT, 2026)
The marriage guardian is an important aspect of Islamic marriage law that has been the subject of disagreement among scholars, particularly between Imam Shafi'i and Imam Hanafi. This difference in opinion has significant legal implications for the validity of marriage, especially regarding the position of guardians for adult women. This study aims to analyze the basis for the differences in opinion between Imam Shafi'i and Imam Hanafi regarding the position of the marriage guardian and its relevance in the development of Islamic family law. The research method used is library research with a legal-normative and historical-conceptual approach, using primary sources in the form of classical fiqh books and secondary sources in the form of books, scientific journals, and relevant laws and regulations. The data was analyzed descriptively, analytically, and comparatively to compare the arguments of the two schools of thought. The results of the study show that Imam Shafi'i established the guardian as an absolute pillar of marriage, so that marriage without a guardian is declared invalid, both for unmarried women and widows, adults and minors. Meanwhile, Imam Hanafi argues that adult women of sound mind can marry themselves without a guardian as long as they meet the requirements of kufu' and a suitable dowry, so that the presence of a guardian is sunnah, not an essential element. The conclusion of this study confirms that these differences of opinion are caused by differences in understanding the arguments of the Qur'an and hadith, as well as the methods of istinbath (derivation of legal rulings) used by each imam, which demonstrates the flexibility of Islamic law in responding to social contexts and community needs.